Should Prenatal Chromosomal Microarray Analysis Be Offered for Isolated Fetal Growth Restriction? A French Multicenter Study. Issue 6 (June 2022) - Monier, Isabelle; Receveur, Aline; Houfflin-Debarge, Véronique; Goua, Valérie; Castaigne, Vanina; Jouannic, Jean-Marie; Mousty, Eve; Saliou, Anne-Hélène; Bouchghoul, Hanane; Rousseau, Thierry; Valat, Anne-Sylvie; Groussolles, Marion; et al.
Abstract : (Abstracted from Am J Obstet Gynecol 2021;225:676.e1–676.e15) One common cause of perinatal mortality is fetal growth restriction (FGR), which is associated with neurodevelopmental impairment, other neonatal morbidities, as well as a risk of adult vascular disease. Estimated fetal weight of <10th percentile for gestational age is generally used as diagnostic criteria for FGR diagnosis.